THE EFFECT OF DIVIDEND POLICY DETERMINANTS WITH SIZE AS A MODERATING VARIABLES IN LQ45 COMPANIES REGISTERED INDONESIAN STOCK EXCHANGE - Marlina Widiyanti; Taufik Taufik; Isni Andriana; Kemas Muhammad Husni Thamrin (President University, 2021)
Dividend policy is of concern to many parties such as shareholders, creditors, and other external parties who have an interest in the information issued by the company. This study aims to analyze the determinants of dividend payout ratio, which is proxied by variables, profitability (ROE), liquidity (CR) and company size (size) as moderating variables in LQ45 companies listed on the Indonesian stock exchange. The population this study were all LQ-45 companies for the period 2016-2018. The sample was determined based on the purposive sampling method so that a sample of 19 companies obtained. The results of this study indicate that return on equity (ROE), current ratio (CR) have positive and significant effect on dividend policy (dividend payout ratio). The MRA test shows that firm size as a moderating variable can influence the relationship between profitability (ROE)and liquidity (CR) on dividend policy (DPR). The results of this study are also in line with the signaling theory which states that companies that pay high dividends will be positive signal for investors because they think the company will experience profits in the future and as an implication of this study the more liquid the company will be, the more internal funds it will receive.Keywords: Dividend Policy, Profitability, Liquidity, and Size (Company Size)